PENGARUH LEVERAGE, ROTASI KAP DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY - Pramono, Adi; Handayani, Asih (Publika Citra Media, 2024)
This study aims to determine and analyze the effect of leverage, KAP rotation and financial distress on audit delay for the period 2018-2022. The research method used is descriptive associative with a quantitative approach. The type of data used is secondary data. The data analysis technique used is multiple linear regression analysis assisted by data processing using e-views software version 12 and the confidence level used is 5%. Based on the results of the study, it shows that leverage, KAP rotation and financial distress simultaneously affect audit delay. Partially, leverage and KAP rotation do not affect audit delay, while financial distress affects audit delay.